Impact of Pluri-Lateral Free Trade Agreements on Innovation: Example of ASEAN - Robert Smith; Nucharee Smith; Mark Perry (JAS (Journal of ASEAN Studies), 2023)
Innovation has been identified as a critical indicator for an economy to succeed in the fourth industrial revolution. Historically, some members of the Association of Southeast Asian Nations have been better known for violation of intellectual rights rather than their protection. However, this is changing as their economies develop and they have been better integrated into the global economy. Integration has been facilitated by their membership of the World Trade Organization and bilateral Free Trade Agreements (FTAs) between individual states and their trading parties. ASEAN has entered into plurilateral FTAs with some of its trade partners. A key element of these plurilateral FTAs is that most dedicate a Chapter on the protection of intellectual property rights. These clauses have two essential elements. Firstly, they set out the obligations of the parties to protect intellectual property rights and their commitment to seek membership of intellectual property treaties. Secondly, the parties undertake to assist the lesser developed members with improving their processes and procedures so that they can accede to appropriate treaties. The research analysed the impact of these multilateral FTAs on the protection of patents and marks by the individual ASEAN members.